A Study of East-Coast Cyclogenesis Employing Quasi-Lagrangian Diagnostics - Conant, Peter R (1982)
The absolute vorticity and angular momentum budgets for the President's Day Cyclone, 18-19 February 1979, are evaluated employing the quasi- Lagrangian diagnostic technique in pressure coordinates. The First GARP Global Experiment (FGGE) Level III-b data set prepared by the European Center for Medium Range Weather Forecasts is used to define the storm and to calculate the budgets. Important differences are found between the FGGE and mass budget vertical motion estimates . The budget results illustrate the importance of inward eddy mode lateral transport and advection at upper levels and mean mode transport due to convergence at lower levels. The vertical redistribution plays a lesser role but is more significant in the angular momentum budget . The vertical vorticity advection and tilting terms are comparable in magnitude. The largest budget residuals occur during the period of most intense convection activity which indicates a need for a better understanding of the vertical redistribution processes.